Analisis Unsur Naratif sebagai Pembentuk Film Animasi Bul - Gede Pasek Putra Adnyana Yasa (Universitas Bumigora, 2021)
Animated films that are interesting and beautiful can be created if an animator or creator, and the audience understand the elements that make up an animated film. Even more so for animators or creators as creators of animated film art. The audience cannot understand the animated film being shown, if the creator himself does not understand the elements that make up the animated film. The animation, entitled Bul, is the best animated film in the 2D animated film category. Therefore, it becomes interesting to be explored or researched. This research was conducted by observing the animated film Bul. This research is a field research designed to study, and reveal how the aesthetics of an animated film Bul is formed by film-forming elements, one of which is the narrative element. The critical paradigm is used as a basis for thinking in the hope of being able to comprehensively reveal and answer the problem of narrative elements in the animated film Bul. This research uses qualitative research methods in the area of ​​art studies, which is a research procedure that produces descriptive data in the form of written words or expressions from a person and studies the behavior of the artist and the object being observed. The results showed that the narrative element which is one of the elements that form a film, especially in this case the animated film entitled Bul, has a very important role. Narrative elements consist of elements of theme, story, story structure, and character/character. Each element is interrelated, supports each other, needs and influences each other so as to create a unity that is able to create a beautiful feeling and the message can be received by the observer or the audience.